2017
DOI: 10.1371/journal.pone.0183604
|View full text |Cite
|
Sign up to set email alerts
|

Restored nitric oxide bioavailability reduces the severity of acute-to-chronic transition in a mouse model of aristolochic acid nephropathy

Abstract: Aristolochic Acid (AA) nephropathy (AAN) is a progressive tubulointerstitial nephritis characterized by an early phase of acute kidney injury (AKI) leading to chronic kidney disease (CKD). The reduced nitric oxide (NO) bioavailability reported in AAN might contribute to renal function impairment and progression of the disease. We previously demonstrated that L-arginine (L-Arg) supplementation is protective in AA-induced AKI. Since the severity of AKI may be considered a strong predictor of progression to CKD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In addition, AA-treated zebrafish embryos showed a blood cell accumulation in the kidney that triggered inflammation, which was evidenced by upregulation of the expression of proinflammatory genes, including tumor necrosis factor alpha (TNFα), cyclooxygenase (COX-2), myeloperoxidase (MPO), and interleukin 1 beta (IL-1β) [72]. Similarly, Jadot and colleagues observed an increase in renal mRNA expression of proinflammatory cytokines, including IL-6, IL-1β, and TNFα, following the treatment of mice with AA [73]. Recently, NLRP3 inflammasome, a multimeric protein complex that initiates an inflammatory form of cell death, has been reported to be implicated in AA-mediated nephrotoxicity.…”
Section: Aa Induces Inflammatory Responsementioning
confidence: 98%
See 2 more Smart Citations
“…In addition, AA-treated zebrafish embryos showed a blood cell accumulation in the kidney that triggered inflammation, which was evidenced by upregulation of the expression of proinflammatory genes, including tumor necrosis factor alpha (TNFα), cyclooxygenase (COX-2), myeloperoxidase (MPO), and interleukin 1 beta (IL-1β) [72]. Similarly, Jadot and colleagues observed an increase in renal mRNA expression of proinflammatory cytokines, including IL-6, IL-1β, and TNFα, following the treatment of mice with AA [73]. Recently, NLRP3 inflammasome, a multimeric protein complex that initiates an inflammatory form of cell death, has been reported to be implicated in AA-mediated nephrotoxicity.…”
Section: Aa Induces Inflammatory Responsementioning
confidence: 98%
“…Nitric oxide (NO) is involved in the regulation of renal blood flow. Studies have reported that AAN is associated with decreased NO bioavailability [73]. In this regard, Declèves and colleagues showed that administration of L-arginine, a precursor of NO, restored its bioavailability and ameliorated AKI in mice treated with AA [50].…”
Section: Other Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…C57Bl/6 J male mice were daily i.p. injected with a solution of AAI (3.5 mg/kg) for 4 days and then sacrificed at 5, 10 or 20 days after the first day of injection [15,39]. The acute phase was identified at day 5 with necrosis of PTEC while at day 20, cystic tubules and tubulointerstitial fibrosis was observed characterizing the features of a chronic phase.…”
Section: Experimental Models Of Aa Intoxicationmentioning
confidence: 99%
“…[15][16][17][18] More importantly, CP is widely used in clinic due to its high efficiency, and to avoid its nephrotoxicity clinicians usually adopt a multiple low-dose administration. [15][16][17][18] More importantly, CP is widely used in clinic due to its high efficiency, and to avoid its nephrotoxicity clinicians usually adopt a multiple low-dose administration.…”
Section: Introductionmentioning
confidence: 99%